(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2022)
The overcurrent phenomena are a dangerous condition that can be occurred in the electrical system and equipment. The condition of the overcurrent will cause the short-circuited current flows through the system and affect the other distribution line. The purpose of this study is to investigate the coordination of the overcurrent relay in different types of the distribution network which are radial distribution system, ring distribution system, and interconnected distribution system during line to ground fault occur at the bus. The generation of the overcurrent and directional overcurrent flow in the distribution network will damage the nearest equipment and reduce the power stability. The installation of the IDMT overcurrent relay in the distribution system will clear the faulty section from affecting the other distribution line. This protective device also operates to detect the abnormal condition with proper time current characteristic condition that involves the optimum time speed, accurate coordination, and sensitivity. The simulation of the IDMT overcurrent relay in the one-line diagram of the distribution network is executed by using ETAP software meanwhile the IDMT relay setting is calculated via MATLAB.